The Association between Duration of Type 2 Diabetes Mellitus with Severity Degrees of Ischemic Stroke Patient in Ward of Neurogical Disease at RSUD Dr. Moewardi - Triono Agung Sakti; . Suroto; Cr Siti . Utari (Nexus Kedokteran Klinik, 2014)
Background: Stroke is a most common cerebrovascular disease which is more common and become the second leading cause of death after ischemic heart disease in the world. In Indonesia, approximately 15.4% of deaths caused by stroke. One of risk factor from stroke is Diabetes Mellitus (DM) and Diabetes Mellitus type 2 is a major part of the diabetes that exist in society, especially in adulthood, which is about 85-90% of all diabetes types in the world. Therefore, it needs systematic examination of the use of the National Institutes of Health Stroke Scale (NIHSS) to determine the severity degrees of stroke in stroke patients who also suffer from diabetes. This study aimed to determine the association between duration of type 2 diabetes mellitus with severity degrees of ischemic stroke patient in Ward Neurological Diseases at RSUD Dr. Moewardi. Methods: This is an observational analytic study using cross sectional approach. A total of 32 subjects were selected by using purposive sampling, and subjects were ischemic stroke patients in Angrek II Ward of Neurological Disease at Hospital Dr. Moewardi. Data were collected by direct interview and examined subject using the NIHSS score. Data were analyzed using multiple logistic regression model and processed with the Statistical Product and Service Solutions (SPSS) for Windows 17:00. Results: Multiple logistic regression analysis showed the results OR = 1.558; 95% CI 0.317 to 7.656, and p = 0.585. These results already control all of confounding variables such as the levels of total cholesterol, smoking history, blood pressure, and history of alcohol consumption. Ischemic stroke patients who also suffer type 2 diabetes mellitus ? 5 years increases the risk of ischemic stroke with severe severity 1,558 times more than patients who have type 2 Diabetes Mellitus <5 years. Conclusions: There is a medium relationship between duration of type 2 Diabetes Mellitus with severity degrees ischemic stroke patient in Ward of Neurological Deisease at RSUD Dr. Moewardi, but the result is not significant in statistic. Keywords: Length Duration of DM, Tipe 2 Diabetes mellitus, Ischemic Stroke, Severity Degrees of Stroke